POSTER ANALYSIS OF PUBLIC SERVICES ADVERTISING BY SEPDIANTO SAPUTRA: STUDY OF SAUSSURE SEMIOTICS - Patriansah, Mukhsin (Arty: Jurnal Seni Rupa, 2020)
The visual appearance contained in a poster has a certain meaning and meaning that it wants to convey to the wider community. Therefore, posters are only limited to media, what is no less important in a poster is the message that is informed. The message conveyed is in the form of visual signs that are used to present a specific purpose and purpose that is useful for mobilizing community solidarity in dealing with a social problem. The visual signs presented in a public advertisement service poster, for example, are very interesting to be traced, dissected and then analyzed using a semiotic approach. Semiotics is a scientific discipline that studies sign systems and how the system works. The sign system that will be dissected and analyzed in this paper is a sign system presented in the form of a public service advertisement poster with the theme "Stop Domestic Violence" by Sepdianto Saputra